Pendidikan Kesehatan Berbasis Audio Visual untuk Meningkatkan Pemahaman Keluarga tentang Pencegahan Luka Tekan - Chayati, Nur; Juandi, Gema Akbar Purnama (Jurnal Kesehatan Komunitas, 2023)
Introduction: Bed rest patients have a high risk of damage to the integrity of the skin caused by pressure and immobilization (bed rest), known as decubitus ulcers or pressure sores. The occurrence of pressure sores is heavily influenced by the level of education and knowledge of patients and families, research objectives: to analyze the effect of providing audio-visual-based health education in increasing family knowledge about pressure sore prevention, method: quasi-experimental research design with pre-test and post-test designs. The population was families who had patients with a high risk of developing pressure sores at PKU Gamping Hospital. The process of taking samples with a quota sampling technique was 15 people for the control group and 15 people for the intervention group. The instruments used were questionnaires and educational media in the form of audio-visual media. Data were collected using a questionnaire and analyzed using the Wilcoxon Test and Mann-Whitney Test, results: family knowledge in the intervention group after being given health education experienced a significant change with p-value = 0.001 (p <0.05), whereas in the control group, it did not have a change with p-value = 0.314 (p>0.05). Audio-visual-based health education influences the level of family knowledge about pressure sore prevention, p-value 0.000 (p <0.05), conclusion: Audio-visual-based health education has a good impact on increasing family knowledge about pressure sore prevention.